2017
DOI: 10.1038/nn.4547
|View full text |Cite
|
Sign up to set email alerts
|

A new fate mapping system reveals context-dependent random or clonal expansion of microglia

Abstract: Microglia constitute a highly specialized network of tissue-resident immune cells that is important for the control of tissue homeostasis and the resolution of diseases of the CNS. Little is known about how their spatial distribution is established and maintained in vivo. Here we establish a new multicolor fluorescence fate mapping system to monitor microglial dynamics during steady state and disease. Our findings suggest that microglia establish a dense network with regional differences, and the high regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
489
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 484 publications
(516 citation statements)
references
References 51 publications
23
489
0
4
Order By: Relevance
“…How this genetic 'memory' in activated microglia affects their function and neuropathic pain remains unknown, but will be important in future research because a recent study in the facial motor nucleus found that some microglia proliferated by PNI persist for approximately two months post-PNI. 34) In summary, our longitudinal and detailed analyses of SDH microgliosis after PNI further characterized a series of their activation. In particular, by using short-pulse labeling of proliferating cells, this study identified for the first time a narrow time window to induce a proliferation burst of SDH microglia after PNI.…”
Section: Discussionmentioning
confidence: 76%
“…How this genetic 'memory' in activated microglia affects their function and neuropathic pain remains unknown, but will be important in future research because a recent study in the facial motor nucleus found that some microglia proliferated by PNI persist for approximately two months post-PNI. 34) In summary, our longitudinal and detailed analyses of SDH microgliosis after PNI further characterized a series of their activation. In particular, by using short-pulse labeling of proliferating cells, this study identified for the first time a narrow time window to induce a proliferation burst of SDH microglia after PNI.…”
Section: Discussionmentioning
confidence: 76%
“…A recent investigation revealed that microglial cell number is tightly controlled by temporal and spatial coupling of apoptosis and proliferation within the microglial population, which provides evidence for tight control of microglial cell numbers (85). Using a novel microglia-fate mapping system, it was shown that in the healthy brain regional differences in microglia self-renewal exist and that microglia expansion is a random process during homeostasis that can shift to clonality upon pathology (86).…”
Section: Physiological Function Of Microglia In the Adult Brainmentioning
confidence: 99%
“…For example, it remains unclear if the self-renewal of PVM takes place through brain-resident progenitors and, if so, the identity of these cells and their relationships to microglia and other brain-resident macrophage populations remain to be defined. Microglial turnover varies regionally and results from a stochastic cell division process in homeostatic conditions and from expansion of selected clones after local microglial proliferation caused by facial nerve transection [71]. It remains unclear if similar processes of self-renewal and expansion, independent of a precursor pool, also are involved in PVM turnover and proliferation.…”
Section: Future Directionsmentioning
confidence: 99%